ANALISIS EFISIENSI INDUSTRI GULA DI INDONESIA DENGAN METODE DATA ENVELOPMENT ANALYSIS (DEA) TAHUN 2001 – 2010 - Silvi Marta; Osni Erza (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2010)
This study aims to determine the efficiency of the sugar industry factories inIndonesia. These plants are PG Jatitujuh, PG Karangsuwung, PG Sindanglaut, PG Subang,PG Tersanabaru, PG Gondangbaru, PG Jatibarang, PG mojo, PG Pangka, PG Rendeng. Data used in this study is secondary data, the source data comes from the Indonesian Sugar Council with the years of the study was taken from 2001 to 2010. Variables used in this study consisted of three input variables and two output variables. Variable input consists of thecane milled, the total area, kapasits rollers, while the output variables consist of sugar production and production drops. The results of processing by using the Data Envelopment Analysis (DEA) in the period 2001-2010 shows that there are only three plants in a row is consistent with maintaining the efficiency of 100%. Three factories are PG Jatitujuh, PGJatibarang and PG Sindanglaut. While the other two factories, namely PG Rendeng and PGGondangbaru showed a decreased efficiency level of performance each year with numbers below 100%.Keywords: Efficiency, DEA, Sugar Company, Total Cane ground, Area, Milling Capacity,Production of Sugar and Molasses Production.